Cracking the SAT. French subject test - Gaden, Monique; Ingram, Simone; Princeton Review (Firm) (New York : Random House, 2007)
Prepares students for the SAT French Subject Test, providing vocabulary, grammar, and reading comprehension reviews, test-taking strategies, drills with explained answers, and two full-length practice tests with explained answers.
At head of title: The Princeton Review.
Spine title: SAT.
Young Adult
Text mainly in English; with some French.
Keywords: College entrance achievement tests -- United States -- Study guides; French language -- Examinations -- Study guides; College entrance achievement tests -- Study guides; French language -- Examinations -- Study guides